Pulmonary artery acceleration time in young children is determined by heart rate and transpulmonary gradient but not by pulmonary blood flow: A simultaneous echocardiography—cardiac catheterization study. Issue 7 (12th June 2022) - Tai, Christiana; Hsieh, Anyir; Moon‐Grady, Anita J.; Keller, Roberta L.; Teitel, David; Nawaytou, Hythem M.
Abstract: Introduction: Pulmonary artery acceleration time (PAAT) is considered useful for the non‐invasive evaluation of pulmonary artery pressure (PAP) and pulmonary vascular resistance (PVR). PAAT is dependent on PAP, PVR, pulmonary artery compliance, stroke volume, and heart rate. Its relative dependency on these determinants may differ between young and older children, raising uncertainty regarding its utility in young children. We aim to identify the primary determinants of the PAAT in children less than 36 months undergoing cardiac catheterization and its utility for the diagnosis of elevated PVR. Methods: We prospectively studied 42 children undergoing cardiac catheterization and simultaneous echocardiography. We determined the correlations of PAAT to the above‐mentioned determinants and evaluated receiver operator characteristic (ROC) curves for diagnosis of PVR indexed to body surface area (PVRi) ≥3 Wu*m 2 . Results: Median age was 11.5 (IQR 5.2, 21.2) months. Moderate correlations were found between PAAT and mean PAP ( R = ‐.66, p < .001), PVRi ( R = ‐.54, p = .004), pulmonary artery compliance ( R = .65, p < .001), transpulmonary gradient ( R = ‐.67, p < .001), stroke volume ( R = .61, p = .002), and heart rate ( R = ‐.63, p < .001). In multivariate regression modeling, only transpulmonary gradient and heart rate were independent determinants of PAAT. PAAT ≤77 msec had acceptable utility for diagnosing PVRi ≥ 3 Wu*m 2 (AUC .8 [.64, .95], n = 36), low sensitivity (59%), and excellent specificity (94%). Conclusion: Transpulmonary gradient and heart rate, but not pulmonary blood flow, are important determinants of PAAT in children <36 months undergoing cardiac catheterization. PAAT has low sensitivity for diagnosing elevated PVRi, therefore, should not be solely relied upon in screening for elevated PVRi in young children.